Juruá Orogeny: Brazil and Andean Countries - Caputo,Mario Vicente (2014)
Seismic data from Petrobras (Brazilian state-owned petroleum company) show wide deformation and many reverse faults throughout the Solimões and Acre basins of northern Brazil. This deformation was observed for the first time in the Juruá River in 1976 in the Solimões Basin, and it increases toward Acre and Subandean basins from Argentine and Chile to Colombia and Venezuela. Structural inversions, block uplifts, and asymmetrical folds are attributed to compression and shearing stresses along this wide area. The severe diastrophism seen in the Juruá River area is of Late Jurassic (Kimmeridgian) age. It probably coincided with the final separation between Laurasia and Gondwana continents and the initial opening of the Central Atlantic Ocean. In Peru and neighboring countries, the same Late Jurassic orogeny is also present. It occurs in the form of widespread regional uplifts, structural inversions, tilting, faults and asymmetrical folds beneath a pronounced regional parallel or angular unconformity of latest Jurassic age, marking a first-order sequence boundary above the Upper Jurassic Sarayaquillo Formation and equivalent formations, as well as above older formations. The depositional hiatus at the upper part of the Jurassic System is attributed to reorganization of stress fields that resulted in basin inversions, followed by widespread peneplanation. The uppermost Jurassic or lower Cretaceous beds, deposited above this regional unconformity, were not affected by this tectonism in Brazilian and Subandean basins. The stratigraphy of Peruvian Subandean sedimentary basins is similar to that of the Acre Basin.